The organisation of nurse staffing in intensive care units: A qualitative study. (10th April 2022) - Endacott, Ruth; Pattison, Natalie; Dall'Ora, Chiara; Griffiths, Peter; Richardson, Annette; Pearce, Susie; ,
Abstract: Aims: To examine the organisation of the nursing workforce in intensive care units and identify factors that influence how the workforce operates. Background: Pre‐pandemic UK survey data show that up to 60% of intensive care units did not meet locally agreed staffing numbers and 40% of ICUs were closing beds at least once a week because of workforce shortages, specifically nursing. Nurse staffing in intensive care is based on the assumption that sicker patients need more nursing resource than those recovering from critical illness. These standards are based on historical working, and expert professional consensus, deemed the weakest form of evidence. Methods: Focus groups with intensive care health care professionals ( n  = 52 participants) and individual interviews with critical care network leads and policy leads ( n  = 14 participants) in England between December 2019 and July 2020. Data were analysed using framework analysis. Findings: Three themes were identified: the constraining or enabling nature of intensive care and hospital structures; whole team processes to mitigate nurse staffing shortfalls; and the impact of nurse staffing on patient, staff and intensive care flow outcomes. Staff made decisions about staffing throughout a shift and were influenced by a combination of factors illuminated in the three themes. Conclusions: Whilst nurse:patient ratios were clearly used to set the nursing establishment, it was clear that rostering and allocation/re‐allocation during a shift took into account many other factors, such as patient and family nursing needs, staff well‐being, intensive care layout and the experience, and availability, of other members of the multi‐professional team. This has important implications for future planning for intensive care nurse staffing and highlights important factors to be accounted for in future research studies. Implications for Nursing Management: In order to safeguard patient and staff safety, factors such as the ICU layout need to be considered in staffing decisions and the local business case for nurse staffing needs to reflect these factors. Patient safety in intensive care may not be best served by a blanket 'ratio' approach to nurse staffing, intended to apply uniformly across health services.